NRT1.1 Regulates Nitrate Allocation and Cadmium Tolerance in Arabidopsis - Jian, Shaofen; Luo, Jingsong; Liao, Qiong; Liu, Qiang; Guan, Chunyun; Zhang, Zhenhua (Frontiers in Plant Science, 2019)
Abiotic stress induces nitrate (NO3-) allocation to roots, which increases stress tolerance in plants. NRT1.1 is broadly involved in abiotic stress tolerance in plants, but the relationship between NRT1.1 and NO3- allocation under stress conditions is unclear. In this study, we found that Arabidopsis wild-type Col-0 was more cadmium (Cd2+)-tolerant than the nrt1.1 mutant at 20 μM CdCl2. Cd2+ exposure repressed NRT1.5 but upregulated NRT1.8 in roots of Col-0 plants, resulting in increased NO3- allocation to roots and higher [NO3-] root-to-shoot (R:S) ratios. Interestingly, NITRATE REGULATORY GENE2 (NRG2) was upregulated by Cd2+ stress in Col-0 but not in nrt1.1. Under Cd2+ stress, nrg2 and nrg2-3chl1-13 mutants exhibited similar phenotypes and NO3- allocation patterns as observed in the nrt1.1 mutant, but overexpression of NRG2 in Col-0 and nrt1.1 increased the [NO3-] R:S ratio and restored Cd2+ stress tolerance. Our results indicated that NRT1.1 and NRG2 regulated Cd2+ stress-induced NO3- allocation to roots and that NRG2 functioned downstream of NRT1.1. Cd2+ uptake did not differ between Col-0 and nrt1.1, but Cd2+ allocation to roots was higher in Col-0 than in nrt1.1. Stressed Col-0 plants increased Cd2+ and NO3- allocation to root vacuoles, which reduced their cytosolic allocation and transport to the shoots. Our results suggest that NRT1.1 regulates NO3- allocation to roots by coordinating Cd2+ accumulation in root vacuoles, which facilitates Cd2+ detoxification.